2016
DOI: 10.4103/0970-9185.168261
|View full text |Cite
|
Sign up to set email alerts
|

Water-cooled radiofrequency neuroablation for sacroiliac joint dysfunctional pain

Abstract: Sacroiliac (SI) joint dysfunction is a common source of chronic low-back pain. Recent evidences from different parts of the world suggest that cooled radiofrequency (RF) neuroablation of sacral nerves supplying SI joints has superior pain alleviating properties than available existing treatment options for SI joint dysfunctional pain. A 35-year-old male had intractable bilateral SI joint pain (numeric rating scale [NRS] – 9/10) with poor treatment response to intra-articular steroid therapy. Bilateral water co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The sacroiliac joint (SIJ) is known to be both a site of load transmission between the spine and lower extremities, and an important contributor to low back and posterior pelvic girdle pain (Schwarzer et al 1995;Robert et al 1998;Fortin et al 1999;Cohen, 2005;Forst et al 2006;Szadek et al 2009;Laplante et al 2012;Cohen et al 2013;Visser et al 2013). In recent years, a number of non-surgical (Dussault et al 2000;Damen et al 2002;Fritz et al 2008;Jee et al 2014;Kasliwal & Kasliwal, 2016;Kurosawa et al 2016) and surgical techniques (Waisbrod et al 1987;Buchowski et al 2005;Al-Khayer et al 2008;Khurana et al 2009;Ebraheim et al 2010;Biswas et al 2016;Duhon et al 2016) have evolved for its treatment. A particular aim is to relieve nerve irritation related to SIJ pathology (Kibsg ard et al 2014a) or to reduce SIJ motion by means of surgical implants (Kube & Muir, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The sacroiliac joint (SIJ) is known to be both a site of load transmission between the spine and lower extremities, and an important contributor to low back and posterior pelvic girdle pain (Schwarzer et al 1995;Robert et al 1998;Fortin et al 1999;Cohen, 2005;Forst et al 2006;Szadek et al 2009;Laplante et al 2012;Cohen et al 2013;Visser et al 2013). In recent years, a number of non-surgical (Dussault et al 2000;Damen et al 2002;Fritz et al 2008;Jee et al 2014;Kasliwal & Kasliwal, 2016;Kurosawa et al 2016) and surgical techniques (Waisbrod et al 1987;Buchowski et al 2005;Al-Khayer et al 2008;Khurana et al 2009;Ebraheim et al 2010;Biswas et al 2016;Duhon et al 2016) have evolved for its treatment. A particular aim is to relieve nerve irritation related to SIJ pathology (Kibsg ard et al 2014a) or to reduce SIJ motion by means of surgical implants (Kube & Muir, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The innervation of the dorsal area of the sacroiliac joint (SI) has been widely reported based on the result of previous studies originating from L4 and L5 dorsal ramus and nerve S1,2,3 and a small portion of S4. [1][2][3][4][5] In this study, the authors prove that PRF ablation performed on the sacroiliac joints decreases >50% of pain scale and is followed by a reduction in the dose of analgesic in patients experiencing sacroiliac joint pain. This result was similar with previous studies.…”
Section: Discussionmentioning
confidence: 94%
“…Although all of these methods, pain relief is a challenger in many cases. 1,2,5 Previous study reported that pulsed radiofrequency denervation of the L4 and L5 primary dorsal rami and S1-3 lateral branches provide significant pain relief and functional improvement compared to intra-articular injection. 14 RF ablation in the sacroiliac joint is an action carried out based on the result of previous cadaver studies stating that there are anastomosed nerves with multiple dorsal primary branches around the neural foramen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation